STRUKTUR KOMUNITAS ARTHROPODA DI EKOSISTEM TANAMAN PADI BERDASARKAN JARAK REFUGIA - Sumini; Hermanto; Sutejo (LPPM Universitas Musi Rawas, 2023)
This study aims to evaluate the community structure of arthropods in the rice ecosystem based on refugia distance. This study used a survey method which was carried out in rice fields owned by rice farmers where there were refugia plants with refugia planting distances from rice plants, namely 0 meters - 2 meters, 2 meters - 4 meters, 4 meters - 6 meters, 6 meters - 8 meters, and 8 meters. meters – 10 meters. Arthropod data or samples were collected in the field using insect nets and brought to the Laboratory of Pests and Diseases, Faculty of Agriculture, Musi Rawas University to be identified. The parameters observed in this study were the types of arthropods found, pest populations in the vegetative and generative phases, and the abundance of natural enemies. The results showed that the types of arthropods found were classified into phytophagous arthropods and predatory arthropods, with 7 species of pests and 6 species of predators. Pest populations in the vegetative and generative phases are dominated by the Acrididae family. Diversity index of predatory arthropods in moderate ecosystems with a high evenness index.